Teacher - Student Interaction In Speaking Class At The First Year Of SMK Muhammadiyah 2 Surakarta In 2011/2012 - Mustikaningsih, Tri (2012)
This study aims at describing: 1) the process of teacher-student interaction in speaking class, and 2) the type of interaction in English speaking classroom. In achieving the objectives, the researcher employed descriptive qualitative as the approach to collect and analyze the data. The research was held in SMK Muhammadiyah 2 Surakarta. The object of the study is the process of speaking classroom interaction of the first year. The writer got the data of the research from event, informant, and document. The techniques of collecting data are the observation, interview, and documentation about the teacher-students interaction process. The results of the analysis show that the process of teaching speaking elicits the students' capability in speaking. By using this technique, the students are able to know their errors, the reason and correct them. So, it facilitates the teacher-student interaction process. There are three types of teacher-students interaction, namely learner-content interaction, learner-instructor interaction, and learner-learner interaction. The researcher finds two types of interactions in the field: learner-instructor interaction, and learner-learner interaction.